2000
DOI: 10.1007/s004150050006
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of fast-FLAIR MRI for lesion detection in the brain of patients with systemic autoimmune diseases

Abstract: Fast fluid-attenuated inversion recovery (fFLAIR) is more sensitive that conventional or fast spin echo T2-weighted magnetic resonance imaging (MRI) for detecting lesions in the brain of patients with ischemic, inflammatory, or demyelinating diseases of the CNS. We investigated whether the use of fFLAIR also increases the sensitivity of brain MRI assessment in patients with systemic autoimmune disorders. Turbo spin echo (TSE) dual-echo and fFLAIR scans of the brain were obtained from patients affected by syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Little is known about the frequency of spinal cord abnormalities in inflammatory disorders and cerebrovascular disease. In one recent study (34), no focal cervical cord lesions were reported on MR images obtained in 44 patients with inflammatory disorders, even though 30% of the images showed brain abnormalities that mimicked MS (35). No comparison was made with patients with cerebrovascular disease, however, and the occurrence of diffuse spinal cord abnormalities was not analyzed.…”
mentioning
confidence: 95%
“…Little is known about the frequency of spinal cord abnormalities in inflammatory disorders and cerebrovascular disease. In one recent study (34), no focal cervical cord lesions were reported on MR images obtained in 44 patients with inflammatory disorders, even though 30% of the images showed brain abnormalities that mimicked MS (35). No comparison was made with patients with cerebrovascular disease, however, and the occurrence of diffuse spinal cord abnormalities was not analyzed.…”
mentioning
confidence: 95%
“…Multiple discrete white-matter lesions in the periventricular, cortical/subcortical junction, and frontal lobe regions are more common in patients with past NPSLE manifestations than in SLE patients without a history of NPSLE 1 . Multiple small periventricular and subcortical white-matter lesions seen by MRI also contribute to severe impairment in tests of strategic cognitive flexibility in patients with current and past NPSLE 5 .…”
mentioning
confidence: 99%
“…Research using structural MRI in SLE patients with longstanding disease has found that small focal lesions concentrated in the periventricular and subcortical white matter are common in patients with NPSLE 14 . Multiple discrete white-matter lesions in the periventricular, cortical/subcortical junction, and frontal lobe regions are more common in patients with past NPSLE manifestations than in SLE patients without a history of NPSLE 1 .…”
mentioning
confidence: 99%
“…The differential diagnosis of WMH is very wide, being associated with many conditions including ageing, dyslipidemia, diabetes, hypertension, heart diseases and migraine 27 . However, many previous reports already proved increased frequency of WMH in SLE and NPSLE 21, 2936 . WMH had been shown to involve preferentially the frontal and parietal lobes, consistent with an anterior to posterior gradient, similar to other causes of WMH, but different from inflammatory demyelinating etiologies such as multiple sclerosis 8, 37 .…”
Section: Introductionmentioning
confidence: 93%